View Of Creed According To Abdullah Bin Abdul Wahhab - Suchi Nurul Khofifah; Fitri Diana Hasibuan; Mat Amin; Panghulu Abdul Karim; Zulfiana Herni (Educare: Journal Educational and Multimedia, 2025)
In the Islamic world in the Middle Ages (1250-1800 AD) ideas of renewal and efforts to purify the faith emerged. Which is a reaction to political conditions and ideology monotheism among the people Islam. On the peninsula Arabia, appear to on the historical stage of a prominent figure, Muhammad ibn 'Abd al-Wahhâb, who had great attention to the issue of purifying faith and reform in Islam. Muhammad ibn 'Abd al-Wahhab's full name is Abu 'Abd Allâh Muhammad ibn 'Abd al-Wahhâb ibn Sulaymân Abu 'Ali b. Muhammad ibn Ahmad ibn Rashid al-Tamimi He born in Nejd, a country Which located in heart field sand that is still pure in its Islam. History books generally reveal that he lived between 1703 and 1787 AD. In the character, knowledge, and life experiences of Muhammad ibn 'Abd al- Wahhâb collected potential For spark his ideas. Thinking Which Its initiation in improving the position of Muslims arose not as a reaction to the political atmosphere as occurred in the Ottoman and Mughal empires, but as a reaction to the understanding of monotheism among Muslims at that time. The purity of their monotheism has been damaged by the teachings of the tarekat since then century 13th spread wide in world Islam. Ideas Muhammad ibn 'Abd al-Wahhâb's efforts to eradicate heresy that entered Islamic teachings eventually developed into a movement called the "Wahabi Movement" .